Multimodal management of giant cerebral aneurysms: review of literature and case presentation. Issue 1 (15th March 2020) - Campos, Jessica K; Ball, Benjamin Z; Cheaney II, Barry; Sweidan, Alexander J; Hasjim, Bima J; Hsu, Frank P K; Wang, Alice S; Lin, Li-Mei
Abstract : The pathophysiology of giant cerebral aneurysms renders them difficult to treat. Advances in technology have attempted to address any shortcomings associated with open surgery or endovascular therapies. Since the introduction of the flow diversion technique, the endovascular approach with flow diversion has become the first-line modality chosen to treat giant aneurysms. A subset of these giant aneurysms may persistent despite any treatment modality. Perhaps the best option for these recurrent and/or persistent giant aneurysms is to employ a multimodal approach—both surgical and endovascular—rather than any single technique to provide a curative result with favourable patient outcomes. This paper provides a review of the histopathology and treatment options for giant cerebral aneurysms. Additionally, an illustrative case is presented to highlight the unique challenges of a curative solution for giant cerebral aneurysms that persist despite initial treatment.